REBOA-Assisted Resuscitation in Non-Traumatic Cardiac Arrest due to Massive Pulmonary Embolism: A Case Report with Physiological and Practical Reflections - Rola, Philippe; St-Arnaud, Philippe; Karimov, Timur; Brede, Jostein Rødseth (Journal of Endovascular Resuscitation and Trauma Management, 2021)
We present the case of a 36-year-old woman who suffered from and ultimately did not survive a non-traumatic out-of-hospital cardiac arrest (NTCA) likely due to massive pulmonary embolism. The resuscitation attempt included the use of a resuscitative endovascular balloon occlusion of the aorta (REBOA) catheter which resulted in a return of spontaneous circulation and distinct improvements in arterial blood pressure, end-tidal CO2 and cerebral oximetry values. This suggests that the use of REBOA has the physiological basis and potential to improve the rate of both survival and favorable neurologic outcome and warrants further study.